Efektivitas Penerapan Lelang Elektronik dalam Mewujudkan Transparansi dan Akuntabilitas Pelayanan Lelang Negara di Indonesia - Ummi Maskanah; Abdullah Gimnastiar; Arfa Maulana; Tami Rai Intan (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines the effectiveness of electronic auction implementation in promoting transparency and accountability of state auction services in Indonesia through the lelang.go.id platform managed by the Directorate General of State Assets. Using normative juridical research. Tthe discussion shows that auction digitalization enhances information disclosure, accessibility and digital documentation (audit trail) that strengthen oversight. However, transparency and accountability are not automatically achieved through technology alone, but depend on regulatory quality, organizer competence, infrastructure readiness and public digital literacy. The study concludes that strengthening institutional governance and internal control remains necessary to optimize the effectiveness of electronic auctions.